Serological and molecular surveillance of infectious bovine rhinotracheitis in Kazakhstan - Karabassova, Aiken; Kirpichenko, Vladimir; Nissanova, Raikhan; Turkeev, Marat; Akylbay, Akmerey; Akshalova, Perizat; Bashenova, Elvira; Tulepov, Bakhyt; Mamanova, Saltanat; Kaimoldina, Saira; Zhapbar, Arailym; Ikramkulova, Fariza; et al. (Frontiers in Veterinary Science, 2026)
IntroductionInfectious bovine rhinotracheitis (IBR), caused by bovine herpesvirus type 1 (BoHV-1), remains endemic in Kazakhstan. Despite the absence of vaccination, comprehensive multi-year data on the virus circulation have been limited.MethodsA three-year surveillance between 2023 and 2025 was conducted in unvaccinated cattle from all 17 administrative regions a total of 8,590 serum samples and 4,795 nasal swabs. Serological monitoring was performed using two validated ELISA systems (IDEXX IBR gE Ab Test and ID Screen® IBR Indirect ELISA). Molecular detection employed real-time PCR on nasal swabs, and virus-isolation attempts were carried out on Vero cell monolayers. National reference serum panels were developed and externally validated at the Friedrich-Loeffler-Institut (Germany).ResultsSerological testing revealed consistently high antibody prevalence—69.13% (2023), 80.64% (2024), and 82.79% (2025)—with marked regional variation. PCR positivity was 11.2% (280/2,500) in 2024 but only 0.43% (10/2,295) in 2025, indicating subclinical circulation and intermittent viral shedding. All virus-isolation attempts were negative, consistent with low viral loads and latent infection. The validated serum panels achieved > 95% concordance with international reference sera and were successfully implemented for national QA/QC.ConclusionThese findings confirm persistent BoHV-1 endemicity in Kazakhstan and highlight the diagnostic and epidemiological framework necessary for harmonized surveillance, DIVA-compatible vaccination (Differentiating Infected from Vaccinated Animals), and progressive alignment with WOAH eradication programs.